Options on the Spot and Options on Futures - BRENNER, MENACHEM; COURTADON, GEORGES; SUBRAHMANYAM, MARTI (Journal of Finance, 1985)
ABSTRACT This paper analyzes and compares the valuation of two types of options that relate to the same asset: options on the asset itself and options on the futures on the asset. The early exercise privilege plays a central role in explaining the differences between the values of the two options. It is shown that in the case of a cash instrument that does not make interim payments, such as gold, the value of a call option on the spot is smaller than the call option on the futures contract; the opposite is true for put options. The early exercise boundaries, which characterize when it pays to exercise, are also compared and analyzed.